Effect of a single Ralgro implant on conception rates and calving difficulty in first calf beef heifers - R.P. Bolze; L.R. Corah; R.J. Pruitt (Kansas Agricultural Experiment Station Research Reports, 1984)
Three hundred and seventy four heifers from two Kansas ranches were used to determine if a single Ralgro implant given either at two months of age or at weaning would influence pelvic development and subsequent calving difficulty or conception rates. The study involved two hers of Simmental (spring and fall calving) and one herd of fall calving Angus cattle. Ralgro did not influence conception rates as yearlings, or percentages of heifers requiring assistance with their first calf. Implanted heifers had larger pelvic areas as yearlings, but the advantage disappeared by two years of age. Pelvic area in assisted vs unassisted two year old heifers did not differ.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Implant; Conception rates; Pelvic area